Leader Effect and Return Stock Market - Kharisya Ayu Effendi; Nugraha Nugraha (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2019)
The purpose of this study is to examine whether the election of Jokowi as the country's leader (president) can affect the stock price return of the Jakarta Composite Index (JCI). The data used in this research is secondary data. Data comes from historical JCI. The data taken is daily data for 12 months before and after Jokowi was appointed president. The data analysis technique used is one t-test sample used to test the first hypothesis and the paired samplest t test was used to test the second hypothesis in this study. The results in testing the paired sample there is no difference in the return of stock prices in the era before and after Jokowi became president.